Red Blood Cell Indices as a Primary Tool for Carrier Screening of Thalassemia & E Disease in Pregnancy - Parveen, Tabassum; Asma, Mahfuja; Akhtar, Nahreen; Sultana, Nigar; Kawsar, Selima; Naznin, Lubna (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Backgrounds: â thalassemia major and Hemoglobin (Hb) E-β thalassemia appears as a significant threat for the health status of a country including Bangladesh. Pregnancy is a state when many women come for antenatal care and complete blood count (CBC) is done as a routine test. The component of this test the red blood cell (RBC) indices include mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC). These measure the size, shape, and physical characteristics of the RBC and can be utilized as a first round screening tool for carrier screening of defective Hb and then subjected to diagnostic testing i.e. Hb-electrophoresis which is a costly and not readily available test in all health facilities. The cutoff value at which the RBC indices are most sensitive and specific for the subsequent diagnostic test was the main objective of this study. Method: This cross sectional study was conducted from January 2023 to July 2023 among pregnant women attended for antenatal care between 10-18 weeks of gestation in the Out Patient Department (OPD) of Fetomaternal Medicine Department of Bangabandhu Sheikh Mujib Medical University. After getting the complete blood count (CBC) report by convenient sampling 112 pregnant women were selected whose MCV value was < 80fl and were subjected to Hb-Electrophoresis to detect defective Hb i.e. â thalassemia and E trait. Result: Cut off value of MCV for detection of defective Hb was 75.1 fl with the sensitivity 81.8% and specificity 64.3%. For MCH best cut off point was 23.5pg with the sensitivity 72.7%% and specificity 62.9%. Conclusion: During pregnancy RBC indices showing MCV ≤75 fl and/or MCH ≤23.5pg should be advised for Hb Electrophoresis for detection of defective Hb in the form of thalassemia trait, E trait or E disease. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 81-90